Use of 6-minute walk test for assessing severity of interstitial lung disease: an observational study: 6MWT for assessing severity of ILD - Hu, Zhan-Wei; Gao, Li; Yu, Qing; Jin, Zhe; Liu, Ju-Hong; Lian, Yuan-Yuan; Que, Cheng-Li (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background: The 6-minute walk test (6MWT) is a potential tool for assessing the severity of interstitial lung disease (ILD). Objectives: To explore the relationship between 6MWT results and traditional measures including pulmonary function and chest computed tomography(CT) and to determine factors that might influence the 6-minute walk distance (6MWD). Methods: Seventy-three patients with ILD were enrolled at Peking University First Hospital. All patients underwent 6MWT, pulmonary CT, and pulmonary function tests and their correlations were analyzed. Multivariate regression analysis was used to identify factors that might impact 6MWD. Results: Thirty (41.4%) of the patients were female and the mean age was 66.1 ± 9.6 years. 6MWD was correlated with forced expiratory volume in 1 second (FEV1), forced vital capacity (FVC), total lung capacity (TLC), diffusing capacity for carbon monoxide (DLCO) and DLCO%pred. The decrease in oxygen saturation (SpO2) after the test was correlated with FEV1%pred, FVC%pred, TLC, TLC%pred, DLCO, DLCO%pred and the percentage of normal lung calculated by quantitative CT. The increase in Borg dyspnea scale was correlated with FEV1, DLCO and the percentage of normal lung. The backward multivariate model (F = 15.257, P < 0.001, adjusted R2 = 0.498) indicated that 6MWD was predicted by age, height, body weight, increase in heart rate, and DLCO. Conclusions: The 6MWT results were closely correlated with pulmonary function and quantitative CT in patients with ILD. However, in addition to disease severity, 6MWD was also influenced by individual characteristics and the degree of patient effort, which should thus be considered by clinicians when interpreting 6WMT results.